تصميمات مقترحة لزي عمال الكي في مصانع الملابس الجاهزة في ضوء المتطلبات الوظيفية - اللهيبي، أفنان عبدالإله عبدالله; جوهر، عماد الدين سيد (الجمعية العلمية للمصممين, 2019)
Ironing workers in garments factories exist in a workplace environment with some factors that reduce worker’s comfort while performing. These circumstances might affect in a way or another workers’ health and safety which eventually reflects on the quality and efficiency of production. The purpose of this study was to analyze the functional requirements of ironing workers uniform and propose five designs for the uniform and assess them in accordance with the nature of the performance and tasks for workers. The study followed the descriptive approach in describing the nature of the work environment in the ironing section and analyzing work tasks and clothing needs for the ironing workers. Survey data were collected from ironing workers in garment factories in Mecca region of Saudi Arabia and experts in the field of clothing and textiles. The findings of this study indicate that the sample of the workers revealed some of workers preferences toward work wear and experts agreed on the third proposed design of the uniform in terms of design and functional aspects which ranked first among the other proposed designs. The study presented a number of recommendations, including: conducting further studies to determine whether the clothing needs of ironing workers differ in areas different from the study, adopting the research methodology (DeJonge method) as a method for designing functional clothing and creating innovative solutions to the work uniforms problems and Studying the aspects of external factors or stress that may affect workers while performing duties in the garment factories.
يتواجد عمال الكي في بيئة عمل يتخللها بعض العوامل التي تقلل راحة العامل أثناء الأداء لاسيما أن الكثير من مصانع الملابس الجاهزة تفتقر إلى توفير زي خاص بعمال الكي تتوفر فيه خواص ومواصفات الأمان والحماية ضد درجات الحرارة المرتفعة والرطوبة والأبخرة الناتجة عن عملية الكي والتي قد تؤثر بصورة مباشرة أو غير مباشرة على سلامة العمال المهنية مما يؤثر على جودة وكفاءة الإنتاج حيث أن القدرة الإنتاجية للعامل قد تتأثر بمستوى الراحة الملبسية. وتتلخص مشكلة البحث وأهدافه في تحليل المتطلبات الوظيفية لزي عمال الكي في مصانع الملابس الجاهزة، ووضع تصاميم مقترحة للزي تتحقق فيه خواص الحماية والأمان وفق القياسات الانثروبومترية بما يتلاءم مع طبيعة الأداء والمهام الوظيفية للعمال. اتبع البحث المنهج الوصفي التحليلي في توصيف طبيعة بيئة العمل في قسم الكي وتحليل مهام العمل والاحتياجات الملبسية لعمال الكي في مصانع الملابس الجاهزة. وتشمل عينة البحث عمال الكي في عدد من مصانع الملابس الجاهزة بمنطقة مكة المكرمة. وأظهرت نتائج البحث اتفاق المتخصصين على ملائمة التصميم الثالث لعمال الكي حيث حصل على المركز الأول من بين التصميمات المقترحة في كلا الجانبين التصميمي والوظيفي. وقد قدم البحث مجموعة من التوصيات أهمها إجراء المزيد من الدراسات لتحديد ما إذا كانت احتياجات عمال الكي الملبسية تختلف عنها في مناطق مغايرة لمنطقة البحث، وتبني المنهج المتبع في البحث (طريقة (DeJonge كمنهج لتصميم الملابس الوظيفية وإيجاد حلول مبتكرة لمشكلات زي العمل، إضافة إلى دراسة الموضوعات التي تعنى بالعوامل الخارجية أو الإجهاد الذي قد يؤثر على العامل في أداء مهامه في مصانع الملابس الجاهزة.
Keywords: الزي الموحد -- مصانع الملابس الجاهزة -- تصميم الملابس -- عمال الكي